A study on present existence and utilization of ponds in a selected area in Jaffna, Sri lanka - Renugapathy, K.; Kuniaki, M. (University of Jaffna, 2017)
Jaffna district is located in dry zone of Sri Lanka. The rainfall of Jaffna is stored as surface water in minor tanks or ponds and recharges the groundwater aquifers. The water is commonly taken out from groundwater aquifer mostly from wells and little from ponds. During the dry season, the water level in wells and ponds decreases to the bottom level. The existence of ponds can be taken as the primary indicator to study the water availability in dry season. The study focused on existence and utilization of ponds in Vadamaradchy East Divisional Secretariat area, where, 10.7 percentages of registered ponds existed in Jaffna district. The primary data were collected through the direct observation and key informant interviews and the secondary data were also collected through the records of Department of Agrarian Services and Department of Irrigation. The utilization of pond plays the multiple roles such as providing water for drinking and cleaning for human, water for agriculture and animals, acting as flood controller and spiritual symbol, establishing freshwater ecosystem in direct way and recharges to the groundwater. The ponds used for agriculture had been reduced by forty and twenty two ponds were given-up as abandoned and no any changes in other uses. The present usage of ponds are limited and maintenance is reduced. Poor maintenance of ponds, construction of private tube well and shallow well at low cost, migration of middle class especially farmers move to abroad, decreased awareness about traditional knowledge and scientific meaning to the traditional knowledge among young people, no mechanism to monitor the maintenance of ponds and the attitude changes of people are the main reasons. The result of the study indicates that the existence of ponds and their maintenance have potential repercussion from changes in social conditions.
Keywords: Existence; Ground water; Ponds; Utilization